2000
DOI: 10.1212/wnl.55.11.1677
|View full text |Cite
|
Sign up to set email alerts
|

MRI, 1H-MRS, and functional MRI during and after prolonged nonconvulsive seizure activity

Abstract: Article abstract-Background: Various structural and functional changes, such as focal edema, blood flow, and metabolism, occur in the cerebral cortex after focal status epilepticus. These changes can be assessed noninvasively by means of MRI techniques, such as fluid-attenuated inversion recovery (FLAIR), EEG-triggered functional MRI (EEG-fMRI), and proton MR spectroscopy (MRS). Methods: The authors report on a 40-year-old patient with nonlesional partial epilepsy in the left posterior quadrant in whom these M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 38 publications
4
39
1
4
Order By: Relevance
“…Concerning the static Cho elevation during FOS activity in epileptic focus compared with the contralateral side, which confirms the results of Lazeyras et al [27] and Lundbom et al [28] (obtained at rest), the result suggests that neuronal tissue subject to prolonged paroxysmal activity may result in membrane damage or gliosis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Concerning the static Cho elevation during FOS activity in epileptic focus compared with the contralateral side, which confirms the results of Lazeyras et al [27] and Lundbom et al [28] (obtained at rest), the result suggests that neuronal tissue subject to prolonged paroxysmal activity may result in membrane damage or gliosis.…”
Section: Discussionsupporting
confidence: 87%
“…Lazeyras et al [27] reported an increase of Cho and Lac and a decrease of NAA in the occipital region of a subject suffering from nonlesional epilepsy in the posterior quadrant immediately following nonconvulsive seizure activity; Cho and Lac levels progressively normalized within 30 days. A similar Cho increase with respect to the region contralateral to seizure was identified with MRS imaging by Lundbom et al [28], who reported also focal increase of Cr and decrease of NAA.…”
Section: Introductionmentioning
confidence: 98%
“…In our WS patients, Cho signals tended to decrease over time but did not differ from those of controls, suggesting the gradual reduction during normal development. Although the Cho signal can be temporarily increased by prolonged epileptic phenomena (Lazeyras et al 2000), signal intensities are not different from controls after the elimination of seizures.…”
Section: Discussionmentioning
confidence: 85%
“…A pial or cortico-pial contrast enhancement can also be disclosed, particularly in larger TPMAs with a subcortical component. In the cases in which a protonic magnetic resonance spectroscopy (MRS) was obtained periictally, the most consistent findings were an increase in the lactate levels and choline and a decrease in N-acetyl-aspartate (Castillo et al, 2001;Lazeyras et al, 2000;Mueller et al, 2001), with the levels of myoinositol possibly fluctuating during and after seizures (Wellard et al, 2003). Generally, these signal abnormalities are colocalized in the same brain regions.…”
Section: Signal Abnormalitiesmentioning
confidence: 97%